Impact of non-commercial recommendations on store attributes salience: an empirical study - Silveira, Paulo Duarte (2019)
The present study aims to investigate the impact of non-commercial recommendation sources on retail store-attributes perceived salience. The study was directed to electronics bricks-and-mortar retail stores. For that purpose, an empirical quantitative study was conducted with face-to-face interviews, using a sample of 555 store customers. In the quantitative hypothesis testing, we correlated the store-attributes perceived salience with the possible non-commercial recommendation sources. The results revealed several positive correlations. Every recommendation source analyzed had between five to thirteen positive significant correlations, out of fifteen possible. The most expressive correlations found were between the variables: the store attribute "cozy/elegant" and the recommendation sources "other customers", "third parties" and "friends or family"; the store attribute "possibility to choose between different models of one product" with the recommendation sources "friends or family", "third parties" and "other customers"; the store attribute "the store carries the latest products" with the recommendation sources "other customers", "friends or family" and "third parties”.